2005
DOI: 10.1063/1.1899986
|View full text |Cite
|
Sign up to set email alerts
|

Quantum integrability of quadratic Killing tensors

Abstract: Quantum integrability of classical integrable systems given by quadratic Killing tensors on curved configuration spaces is investigated. It is proven that, using a "minimal" quantization scheme, quantum integrability is insured for a large class of classic examples.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(77 citation statements)
references
References 33 publications
3
74
0
Order By: Relevance
“…An even more difficult task would be to check whether the classical integrability survives to quantization in the sense of [4].…”
Section: Resultsmentioning
confidence: 99%
“…An even more difficult task would be to check whether the classical integrability survives to quantization in the sense of [4].…”
Section: Resultsmentioning
confidence: 99%
“…families of different metrics having the same un-parametrized geodesics) have been studied intensively by Matveev, Bolsinov, Topalov [4,20] and other authors. In particular, they showed that these metrics are integrable, can be quantized into integrable SDS of type (p, 0, 0) in our sense, and are essentially the same as the so called (separable Stäckel-) Benenti systems studied by Benenti and many other authors in classical and quantum mechanics, see, e.g., [2,4,6,20]. The metrics (induced from R n ) on multi-dimensional ellipsoids belong to this family of integrable metrics, and so the Brownian motion on a p-dimensional ellipsoid is an integrable SDS of type (p, 0, 0).…”
Section: 4mentioning
confidence: 99%
“…Transforming the formulas given in [14] we obtain the integrals (6). Let us compare with Koenigs results 1 , given in [12] p. 378.…”
Section: Part I the Trigonometric Case 1 Local Structurementioning
confidence: 99%
“…The simplest and most natural quantization is certainly Carter's (or minimal) quantization (see [6]). Denoting by a hat the quantum operators and setting = 1, the quantization rules are:…”
Section: Part IV Quantum Aspects 1 Carter Quantizationmentioning
confidence: 99%
See 1 more Smart Citation